Rural Development Indicators Evaluation in Khabat District Educational Services as a Case Study (A Study in Rural Geography) - Ahmed , Hogir Jamil (Zanco Journal of Human Sciences, 2024)
Educational development is one of the objectives of rural development, as it plays a major role in eliminating illiteracy and providing schools and even in the sense of gender in the minds of the villagers, it is clear that this service is available in the villages of Khabat District. therefore, the aim of this study is to highlight the situation in Primary school education is available to reveal the extent to which there is equity in the distribution of educational services, in addition to working to identify functional skills and identify barriers to achievement In addition to its objectives, this study relies on descriptive and analytical methods, including The research is divided into four main themes, which include the theoretical framework of the research, as well as the distribution and differences of place for educational services and functional skills, it is worth mentioning the research area In the academic year (2022-2023), in terms of the number of schools, only (66) Mixed schools have the highest percentage of 95.5% of all types of schools, and the number of boys is higher than that of girls, while the number of female teachers is higher than that of girls There are more males, in addition to the shortage in the number of school buildings, in addition to the villages that are not served They are schools in 10% of the villages in the district. All the indicators are below the education planning criteria, except for the indicator (teacher/student) which is above the criteria Ease of access and time to schools are mostly above education planning criteria, which reflects It creates negativity in the educational process.